Recognition of Fresh Human Tumor by Human Peripheral Blood Lymphocytes Transduced with a Bicistronic Retroviral Vector Encoding a Murine Anti-p53 TCR - Cohen, Cyrille J. (2005)
The p53 protein is markedly up-regulated in a high proportion of human malignancies. Using an HLA-A2 transgenic mouse model, it was possible to isolate high-avidity murine CTLs that recognize class I-restricted human p53 epitopes. We isolated the α- and β-chain of a TCR from a highly avid murine CTL clone that recognized the human p53(264–272) epitope. These genes were cloned into a retroviral vector that mediated high efficiency gene transfer into primary human lymphocytes. Efficiencies of >90% for gene transfer into lymphocytes were obtained without selection for transduced cells. The p53 TCR-transduced lymphocytes were able to specifically recognize with high-avidity, peptide-pulsed APCs as well as HLA-A2.1(+) cells transfected with either wild-type or mutant p53 protein. p53 TCR-transduced cells demonstrated recognition and killing of a broad spectrum of human tumor cell lines as well as recognition of fresh human tumor cells. Interestingly, both CD8(+) and CD4(+) subsets were capable of recognizing and killing target cells, stressing the potential application of such a CD8-independent TCR molecule that can mediate both helper and cytotoxic responses. These results suggest that lymphocytes genetically engineered to express anti-p53 TCR may be of value for the adoptive immunotherapy of patients with a variety of common malignancies.